Meta‐analysis of problem solving therapy for the treatment of major depressive disorder in older adults. (5th October 2015) - Kirkham, Julia G.; Choi, Namkee; Seitz, Dallas P.
Abstract : Objective: Major depressive disorder (MDD) affects many older adults and is associated with poor medical and mental health outcomes. Problem Solving Therapy (PST) has emerged as a promising psychotherapy for MDD in older adults, although the efficacy of PST in this population has not been well described. We examined the effectiveness of PST for the treatment of MDD in older adults in a systematic review and meta‐analysis. Methods: We searched electronic databases to identify randomized controlled trials comparing PST to a control condition or other treatment for MDD in adults with an average age of 60 years or older. We used meta‐analysis to arrive at pooled summary measures of the efficacy of PST when compared to control conditions on the change in depressive symptoms and other outcomes. Results: Nine studies with a total of 569 participants (290 PST, 279 control) met inclusion criteria. Most studies administered PST in person and were between 6 and 12 weeks in duration. Meta‐analysis of six studies evaluating the effect of PST on depression using the Hamilton Rating Scale for Depression identified a significant reduction in depression associated with PST (pooled mean difference = −6.94, 95%CI −10.91 to −2.97, d  = 1.15, P  = 0.0006). PST was also effective in reducing disability in studies reporting this outcome. Conclusions: Our review supports the existing research literature on PST suggesting that it is an effective treatment for older people with MDD. Further study is required to understand long‐term outcomes associated with PST and its efficacy when compared to other treatments. Copyright © 2015 John Wiley & Sons, Ltd.